Cellular markers indicative of ozone stress on bioindicator plants growing in a tropical environment - Alves, Edenise Segala; Moura, Barbara Baesso; Vaz Pedroso, Andrea Nunes; Tresmondi, Fernanda; Machado, Silvia Rodrigues [UNESP] (Elsevier B.V., 2016)
Ozone (0(3)) is an oxidative pollutant that causes visible foliar symptoms in sensitive plants. Importantly, cellular markers induced by physiological alterations, including oxidative burst (OB), hypersensitive response-like (HR-like) reactions, and accelerated cell senescence (ACS), precede these symptoms. Because little is known about the effects of ozone in tropical environments, we aimed to identify these cellular markers in Nicotiana tabacum, lpomoea nil and Psidium guajava growing in an urban area of tropical Sao Paulo, Brazil, and describe the specific physiological alterations that trigger the development of visible symptoms. Cell wall wart-like protrusions, an OB cellular marker, and swelling of thylakoids and mitochondrial membranes, as well as accumulation of plastoglobuli, all markers of ACS, were cell markers common to all species studied. Cellular markers indicating HR-like reaction, as observed in the asymptomatic leaves of N. tabacum and L nil, are precursors of future development of necrotic areas, featuring the visible symptoms. On the other hand, the main cause of visible symptoms in P. guajava appeared to be the accumulation of phenolic compounds in the mesophyll tissue, an ACS marker. Based on this line of evidence, these bioindicator plants growing in a tropical environment show the damaging effects of 03 pollution, even before visible symptoms develop. Moreover, this damage can be detected through a distinct group of cellular markers. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Nicotiana tabacum; Ipomoea nil; Psidium guajava; Oxidative stress